THE ANALYSIS OF ORGANIZATIONAL CULTURE WITH THE DENISON MODEL (The Case Study of Latvian Municipality) - Kokina, Irena; Ostrovska, Inta (European Scientific Journal, ESJ, 2014)
The article is devoted to the study of organizational culture, this is being considered as a problematic topic in management but it requires a wise management. Culture should not be considered as an obstacle in business. In time of competitiveness and changes it has some advantages (Hoecklin, 1994). The culture of a particular organization determines the image of organization as a social institution, and a belonging of human resources to it. This is particularly significant for the state governance and is a source of stability. It can be viewed as a source of inspiration for the employees. Cross-cultural management is a part of international management system that separates itself from the usual (anthropological) view toward culture and can be viewed in the context of practical management. It allows viewing culture as a multi cultural management in all environments. This new approach allows knowledge transfer and organizational learning. The main task of a cross-cultural management is to coordinate professional activity and a professional development of coworkers at the workplace, when knowledge, values and the experience are significant aspects that are to be considered in a multicultural society. Research indicates that culture is seen as a tool that allows describing diverse socio cultural systems. This article is aimed to describe organizational culture in one of the Municipalities with the help of Denison model. The authors analyze organizational culture based on answers of respondents, by taking into account Denison model’s factors and indices that influence organizational culture as relevant for Latvia. This allows reevaluating the quality of culture as a substantial essence, and to determine organizational coherence, integrity and team work. The authors explored the strategy of an organization and how it reacts to changes and integration issues. The number of involved respondents comprises 63 Municipality workers.